Cycles in Stone Mining and Copper Circulation in Europe 5500–2000 bc: A View from Space. (May 2021) - Schauer, Peter; Shennan, Stephen; Bevan, Andrew; Colledge, Sue; Edinborough, Kevan; Kerig, Tim; Parker Pearson, Mike
Abstract : The authors of this article consider the relationship in European prehistory between the procurement of high-quality stones (for axeheads, daggers, and other tools) on the one hand, and the early mining, crafting, and deposition of copper on the other. The data consist of radiocarbon dates for the exploitation of stone quarries, flint mines, and copper mines, and of information regarding the frequency through time of jade axeheads and copper artefacts. By adopting a broad perspective, spanning much of central-western Europe from 5500 to 2000 bc, they identify a general pattern in which the circulation of the first copper artefacts was associated with a decline in specialized stone quarrying. The latter re-emerged in certain regions when copper use decreased, before declining more permanently in the Bell Beaker phase, once copper became more generally available. Regional variations reflect the degrees of connectivity among overlapping copper exchange networks. The patterns revealed are in keeping with previous understandings, refine them through quantification and demonstrate their cyclical nature, with additional reference to likely local demographic trajectories.